Coupling two enzymes into a tandem nanoreactor utilizing a hierarchically structured MOF. Issue 12 (1st August 2016) - Lian, Xizhen; Chen, Ying-Pin; Liu, Tian-Fu; Zhou, Hong-Cai
Abstract : A hierarchically structured MOF is utilized to couple two enzymes in a tandem manner. A stepwise encapsulation with a specific order is the only way to achieve this goal. Abstract : A hierarchical porous metal–organic framework (MOF), PCN-888, containing three types of cavities was utilized to couple two enzymes into a tandem nanoreactor. The largest cavity (6.2 nm) can only accommodate one molecule of glucose oxidase (GOx). The intermediate cavity (5.0 nm) can accommodate one and only one molecule of horseradish peroxidase (HRP). The small cavity (2.0 nm) has sufficient size for neither GOx nor HRP, and remains open as a substrate diffusion pathway. The coupling of the two enzymes can only be achieved through a unique stepwise encapsulation with a specific order (GOx first, followed by HRP). The tandem nanoreactor shows excellent catalytic performances and negligible enzyme leaching. Its catalytic activity is well maintained within several catalytic cycles. Moreover, PCN-888 can provide protection to the encapsulated enzymes against trypsin digestion, indicating the in vitro and in vivo stability of the nanoreactor.